Maintaining & evolving successful commercial Web sites managing change, content, customer relationships, and site measurement - Friedlein, Ashley (Amsterdam ; Boston : Morgan Kaufmann Publishers, 2003)
Ashley Friedlein's first book, Web Project Management: Delivering Successful Commercial Web Sites, became a bestseller and an essential reference for Web professionals developing new sites. Maintaining and Evolving Successful Commercial Web Sites addresses the realities of successful sites today, namely the notion that maintaining and evolving a site is actually a bigger commitment than launching it. Management wants to maximize returns and obtain reliable performance data, customers demand better service and insist on sites that are more advanced yet easier to use, and the Web site must increasingly be integrated with the entire business even as the amount of information it handles continues to grow. Maintaining and Evolving Successful Commercial Web Sites focuses more on process, reality, and pragmatism and less on strategic theory. It provides the reader with the knowledge, tools, approaches, and processes to manage key site maintenance and evolution projects, providing answers to the following questions: *How can I better manage changes and updates to the Web site? *How can I scale up to allow more contributions to the site and more content and still maintain quality and control? *What is content management and how do I go about it? *How do I go about personalization or community building? *What is Customer Relationship Management (CRM) and how do I actually do it online? *How do I measure and report on how well the site is doing? *How do I avoid information overload? *How do I maximize the value the site creates? The book includes case studies to demonstrate candidly how the issues discussed in the book translate into reality. *Case studies show candidly how the issues discussed translate into reality. *Describes content management & Customer Relationship Management (CRM) how to go about implementing them. *Teaches how to measure & report on how well the site is doing, how to avoid information overload, & how to maximize the value the site creates.
Reviewing and reporting progress -- Procedures for managing site updates -- Introducing content management -- Content management in action : a practical example -- Key concepts and building blocks -- Content management systems (CMS) -- Tackling a content management project -- A CRM primer -- Understanding your users -- Personalization -- Community -- Customer service -- The promises and challenges of web site measurement -- The evolution of e-intelligence -- Measurement approaches and techniques -- Reporting and analysis -- How to improve a web site -- Tackling a web site measurement project.
Includes bibliographical references and index.
Keywords: Web sites -- Management; Electronic books